Tonic GABAA conductance decreases membrane time constant and increases EPSP-spike precision in hippocampal pyramidal neurons - Wlodarczyk, Agnieszka I.; Xu, Chun; Song, Inseon; Doronin, Maxim; Wu, Yu-Wei; Walker, Matthew; Semyanov, Alexey (Frontiers in Neural Circuits, 2013)
Because of a complex dendritic structure, pyramidal neurons have a large membrane surface relative to other cells and so a large electrical capacitance and a large membrane time constant (τm). This results in slow depolarizations in response to excitatory synaptic inputs, and consequently increased and variable action potential latencies, which may be computationally undesirable. Tonic activation of GABAA receptors increases membrane conductance and thus regulates neuronal excitability by shunting inhibition. In addition, tonic increases in membrane conductance decrease the membrane time constant (τm), and improve the temporal fidelity of neuronal firing. Here we performed whole-cell current clamp recordings from hippocampal CA1 pyramidal neurons and found that bath application of 10 µM GABA indeed decreases τm in these cells. GABA also decreased first spike latency and jitter (standard deviation of the latency) produced by current injection of 2 rheobases (500 ms). However, when larger current injections (3-6 rheobases) were used, GABA produced no significant effect on spike jitter, which was low. Using mathematical modelling we demonstrate that the tonic GABAA conductance decreases rise time, decay time and half-width of EPSPs in pyramidal neurons. A similar effect was observed on EPSP/IPSP pairs produced by stimulation of Schaffer collaterals: the EPSP part of the response became shorter after application of GABA. Consistent with the current injection data, a significant decrease in spike latency and jitter was obtained in cell attached recordings only at near-threshold stimulation (50% success rate, S50). When stimulation was increased to 2- or 3- times S50, GABA significantly affected neither spike latency nor spike jitter. Our results suggest that a decrease in τm associated with elevations in ambient GABA can improve EPSP-spike precision at near-threshold synaptic inputs.